Peran Pekerja Sosial dalam Proses Pengangkatan Anak di Dinas Sosial Kabupaten Tangerang - Fitriarohmah, Desy; Nurusshobah, Silvia Fatmah; Hakim, Moch Zaenal (Politeknik Kesejahteraan Sosial Bandung, 2024)
The purpose of this study was to determine the role of social workers in the child adoption process. The approach used in this study was qualitative with descriptive methods. The data sources in this study were the Head of LKSA Amanah Assodiqiyah, two families who were adopting children, two social workers, and the Head of the Social Rehabilitation Division of the Tangerang Regency Social Service. Data collection was through in-depth interviews, non-participatory observation, and documentation studies. The aspects studied were how the role of social workers was in the consultation process, administration, surveys/home visits, making social reports and final assessments. Based on the results of the study, it showed that social workers encountered several obstacles that were faced so that they were not optimal in carrying out their roles, including differences in workload and the lack of social workers who had knowledge and skills in the field of child adoption. Based on the results of the study, the researcher proposed a program design, namely